Kontrol diri dan tawakal terhadap quarter-life crisis pada santri di pesantren - Huda, Miftahul (UIN Maulana Malik Ibrahim Malang, 2023)
The phenomenon of quarter-life crisis is part of the growth process of almost all individuals in the adolescent development phase towards early adulthood. Therefore, this study aims to determine the influence of self-control and tawakal on individuals who experience quarter-life crisis. This study consists of three variables: self-control, tawakal, and a quarter-life crisis. The quarter-life crisis was the dependent variable, and self-control and tawakal as the independent variable. This study uses quantitative research methods with a correlational research approach. The sampling technique uses purposive sampling. There are 103 students as a population and 50 samples of students of Pesantren Al-Hikmah Al Fathimiyyah Malang from the calculations using the Slovin formula. The analysis technique used in this research is a descriptive analysis using the R Studio application. The results of this study show that control and tawakal play a role in individuals dealing with quarter-life crises. The effect of self-control and tawakal on the quarter-life crisis is 71.4%, while the remaining 28.6% is outside of the variables studied, namely self-control and tawakal.KEY WORDS: self-control; tawakal; quarter-life crisis; studentsABSTRAKFenomena quarter-life crisis menjadi bagian proses pertumbuhan hampir seluruh individu di fase perkembangan remaja menuju dewasa awal. Oleh karena itu, penelitian ini bertujuan untuk memaparkan bentuk pengaruh self control dan tawakal pada individu yang mengalami quarter-life crisis. Penelitian ini terdiri dari tiga variabel yaitu kontrol diri, tawakal, dan quarter-life crisis. Quarter-life crisis sebagai variabel dependen, kontrol diri, dan tawakal sebagai variabel independen. Penelitian ini menggunakan metode penelitian kuantitatif dengan pendekatan penelitian korelasional, teknik pengambilan sampel memakai purposive sampling, terdapat 103 jumlah santri sebagai populasi dan 50 sampel santri Pesantren Al Hikmah Al Fathimiyyah Malang dari hasil perhitungan menggunakan rumus Slovin. Teknik analisis yang digunakan dalam penelitian ini yaitu analisis deskriptif dengan menggunakan aplikasi R Studio. Hasil penelitian ini yaitu self control dan tawakal berperan bagi individu untuk menghadapi masa quarter-life crisis. Pengaruh self control dan tawakal terhadap quarter-life crisis sebesar 71,4% sedangan sisanya sebesar 28,6% di luar dari variabel yang diteliti yaitu self control dan tawakal.KATA KUNCIkontrol diri; tawakal; quarter-life crisis; santri Copyright ©2023. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0